CORRELATION OF OVARIAN RESERVE PARAMETERS ITS DYNAMICS IN WOMEN WITH INFERTILITY - CHAKRABARTI, SUDAKSHINA; KUMAR, J. VIJAY; HARMA, NIDHI S (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Background: The capacity of human ovaries to produce eggs for healthy viable pregnancy is also term as reproductive potential of ovaries or ovarian reserve. There are a few measurable markers which can determine the capacity of the ovaries. In this study the parameters measured are AMH, D2 AFC, E2, and these are correlated with each other and with BMI and age of the women seeking help for both primary and secondary infertility. Aim and Objectives: To assess the interrelationship of various biochemical and ultrasound markers in infertile women of age group 24-35 years of age. To determine t the correlation of the ovarian reserve parameters with BMI in overweight and obese groups. Methods: Cross-sectional study was conducted on 64 women seeking help for infertility attending Gynecology OPD with no history of PCOS, tubal infertility, contraception, endometriosis, male factor infertility, currently breast fed was excluded from the study. The initial assessment was done by obtaining menstrual history, general physical examination and height, weight of each study subjects. BMI was calculated. Patients selected after meeting the inclusion and exclusion criteria were asked to come on Day 2 or 3 of their cycle for investigations. Blood samples were collected for AMH and E2 estimation on Day 2 or 3 and basal transvaginal 2D USG was done to note the D2 or 3 AFC. The data collected was statistically analyzed for determining the correlation coefficient for each binary group of parameters and the dynamics was represented in tabular form. Results: The interrelation of the parameters studies were determined first in the entire study subjects and the in two groups which were 1. Healthy BMI group, 2. Obese and overweight BMI group. In the entire study subject group AMH had a strong positive correlation with Antral follicle count on D2 or D3 of the cycle of r value +0.83. AMH had a strong negative correlation with D2,3 E2 levels of r value -0.63. The mean AMH and D2 AFC had lesser values 2,44 ng/ml and 13.49 respectively in overweight obese subset than in healthy subset which were 2.64 ng/ml and 16.43 respectively, similarly the mean of E2 levels were higher in obese overweight subset 118.23 pg/ml than in healthy subset 102.43 pg/ml. Conclusion: This study is about the inter relation of the ovarian reserve parameters has been extensively analysed to determine its relationship with Age and BMI of women attempting to conceive.